PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA MENYEBARKAN BERITA BOHONG DALAM UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Afni, Annisa Nur (Yayasan Daarul Huda Kruengmane, 2021)
Fake news is information that is not true, but is made as if it is true, information that is intentionally misleading also does not have a factual basis, but is presented as if it were a series of facts. Fake news is also very vulnerable to invite conflict between communities, moreover it can cause damage to the unity and integrity of the Indonesian nation and as a result of fake news will also cause losses. This study aims to find out and describe the criminal responsibility of the perpetrators of the crime of spreading false news and evidence in the crime of spreading false news. The method used in this research is Normative (Normative Legal Research). This type of research uses qualitative research. The research approach that is carried out is more aimed at the statute approach. Conceptual Approach The nature of the research in this thesis is descriptive research. The form of this research is a prescriptive form. The results of this study indicate that criminal responsibility for the perpetrators of spreading fake news who is ensnared by the Electronic Information and Transaction Law does not only limit the main maker or the first person to spread it, but can be imposed on related parties who participate in disseminating the news. the lie. Criminal liability for spreading false news according to Law Number 19 of 2016 concerning Electronic Information and Transactions can be imposed under Article 45 paragraph (3) and Article 45A paragraphs (1) and (2). Evidence in the criminal act of spreading false news (hoax), not only applies the evidence contained in Article 184 of the Criminal Procedure Code, but also in Article 5 of the Electronic Information and Transaction Law which states that Electronic Information and Electronic Documents and/or their printouts are also evidence. legitimate. It is recommended to law enforcers that legal arrangements regarding the crime of spreading false news in Indonesia need to be improved by adding articles that are able to answer all the needs of the community, both in the Criminal Code and the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transaction.